EFFECT OF THE ADDITION OF ORANGE PEEL POWDER ON THE PHYSICAL AND MECHANICAL PROPERTIES OF POLYLACTIC ACID (PLA)/CELLULOSE ACETATE (CA) FILM COMPOSITES - As-syirazi, Achmad Syarafuddin; Riantoro, Geraldi; Syahjaya, Farhan Alif; Rahmayetty, Rahmayetty; Nuryoto, Nuryoto (Jurnal Rekayasa Kimia & Lingkungan, 2023)
Conventional plastics are already a popular packaging material in society, but they have a harmful influence on the environment. As a result, there is a need for environmentally friendly polymers that are raw from nature and biodegradable alternatives to traditional plastics, one of which is raw plastic Polylactic Acid (PLA) coupled with Cellulose Acetate (CA) and Tween 80 as a compatibilizer. The goal of this research was to find the best ratio of orange skin powder to PLA/CA with the compatibilizer Tween 80 to improve the physical, mechanical, and antibacterial properties of the composite film. The method used is solvent casting with a mass ratio of PLA/CA 6: 4 with the addition of Tween 80 2%, and the addition of orange peel powder with variations of 2, 4, 6, and 10 % w/w to the weight of PLA. The tests carried out include FTIR, SEM, XRD, DSC-TGA, mechanical tests (tensile strength and elongation at break), swelling tests, and antibacterial tests. The results showed that the PLA/CA/Tween 80 film composite has a fairly smooth surface with a small cavity, capable of degrading to a temperature of 546.57C. Regarding the mechanics, the best film composites were identified at a variation of 6% with tensile strength of 4.05 MPa and elongation at break reaching 11.2% with a fairly small water absorption and this variation did not show antibacterial activity.